2015
DOI: 10.1039/c4nr05738d
|View full text |Cite
|
Sign up to set email alerts
|

PSMA-mediated endosome escape-accelerating polymeric micelles for targeted therapy of prostate cancer and the real time tracing of their intracellular trafficking

Abstract: The cytotoxicity of chemotherapeutic agents to healthy organs and drug resistance of tumor cells are believed to be the main obstacles to the successful cancer chemotherapy in the clinic. To ensure that anticancer drugs could be delivered to the tumor region, are quickly released from carriers in tumor cells and rapidly escape from endo/lysosomes, YPSMA-1-modified pH-sensitive polymeric micelles, which would be advantageous in recognizing the prostate specific membrane antigen (PSMA), were designed and fabrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
65
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 53 publications
7
65
0
Order By: Relevance
“…32,38 After which, the mixture was cooled down to room temperature, and the reaction was quenched by adding 10 equiv of methanolic KOH followed by reflux overnight with stirring. 28 Then the resultant mixture was filtered through Sabouraud funnel for 3 times to remove salts.…”
Section: Synthesis and Characterization Of End-group-carboxylated Peomentioning
confidence: 99%
See 1 more Smart Citation
“…32,38 After which, the mixture was cooled down to room temperature, and the reaction was quenched by adding 10 equiv of methanolic KOH followed by reflux overnight with stirring. 28 Then the resultant mixture was filtered through Sabouraud funnel for 3 times to remove salts.…”
Section: Synthesis and Characterization Of End-group-carboxylated Peomentioning
confidence: 99%
“…30 Our previous work and other report demonstrated that this property of PEOz promoted the release of drugs from micelles at the acidic endocytic pH in which PEOz composed the outer shell. 31,32 In order to integrate the merits of PDC for reduced drug release in circulation, and pH-sensitive micelles for enhanced accumulation in tumor site and quick drug release in tumor cells, we fabricated dual endosomal pH-sensitive PDC micelles to encapsulate DOX based on the conjugate of DOX with PEOz via hydrazone linkers (denoted as PEOz-hyd-DOX). Schematic illustrations depicting the formation of pH-sensitive micelles and the intracellular trafficking were presented in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…This method has been rather parsimoniously used in the synthesis of α‐functional PAOx. Example of protecting groups incorporated in cROP initiators include N ‐alkylphthalimide or tert ‐butyl N ‐monoalkylcarbamate (for amines), [ 52–56 ] tert‐ butyldiphenylsilyl ethers (for hydroxyl), [ 57 ] methyl ester (for carboxylic acid or others through amidation), [ 58–63 ] and furanyl Diels–Alder cycloadduct (for maleimide). [ 64 ] Here, the thioacetate group has been chosen as a stable and economic protection group for thiols.…”
Section: Methodsmentioning
confidence: 99%
“…PTX-loaded polymeric micelles (denoted as PTX/PM) were prepared by film-hydration method as previously reported [22]. The ratio of HOOC-PEOz-PLA to paclitaxel was 10:1 (w/w).…”
Section: Preparation Of Drug-loaded Polymeric Micellesmentioning
confidence: 99%